Sexual Satisfaction and its Related Factors in Primigravidas - Ahmadi Z; Molaie Yarandi E; Malekzadegan A; Hosseini AF (Iran University of Medical Sciences, 2011)
Background & Aim : Pregnancy and childbirth is one of the most important stages of women's life. Sexual satisfaction may change during pregnancy. These changes could lead to negative long effects on mother's sexual and mental health. This study was conducted with the aim of assessing sexual satisfaction o f primigravidas and its related factors.   Material & Methods: It was a descriptive cross-sectional study. The sample consisted of 230 primigravid women admitted to hospitals affiliated with Tehran University of Medical Sciences. Data was collected by the adjusted version of Hudson's Index of Sexual Satisfaction (ISS) and were analyzed using SPSS-PC (v.14).   Results: The mean score for sexual satisfaction was 133.6±11.2. The findings indicated that there is a significant relationship between women's age, their husbands' age, length of marriage, occupation, planned/ unplanned pregnancy, type of family, consultant with midwives, having pregnancy complication and concerning about fetus and sexual satisfaction(p<0.0001-0.006)   Conclusion: Helping primigravidas to get more sexual pleasure during pregnancy would be accomplished by taking their sexual histories and resolve their misconceptions about sexual satisfaction.